Insights into poxviruses: virology and vaccines - Adriana Manuka; Irsida Mehmeti; Antonia Radaelli; Eduart Hashorva; Carlo Zanotto; Carlo De Giuli Morghen (Acta Virologica)
Due to the successful eradication of smallpox worldwide and the cessation of smallpox vaccination campaign in 1980, the human population seems to be more susceptible to poxvirus infection. In the last years, an increased detection of zoonotic orthopoxviruses (OPXVs) has also been observed. In particular, in the past 50 years, a high incidence of monkeypox virus (MPXV) disease (MPOX) in both Central and Western Africa was reported. MPXV is not as lethal as variola virus (VARV), the etiological agent of smallpox, but it represents a threat to public health. The global events of MPOX in May 2022, and the ongoing outbreaks in Central and Western Africa in August 2024, have prompted the World Health Organization (WHO) to declare MPXV a Public Health Emergency of International Concern. Preventive vaccination remains the most effective control against MPXV. Smallpox vaccines of the second and third generations have been suggested for high-risk groups, in spite of several limitations, such as some adverse events, reduced immunogenicity, and manufacturing issues. The emerging threat of MPXV highlights the urgent need for the development of vaccines that can effectively control MPOX and potentially prevent diseases caused by other related OPXVs. Our study aims at introducing basic information on the biology of poxviruses, and on factors that may contribute to the reemergence of zoonotic poxviruses. It also summarizes the evolution of vaccinia-based vaccines and strategies that may control and prevent future outbreaks.